2002
DOI: 10.1177/021849230201000229
|View full text |Cite
|
Sign up to set email alerts
|

A Technique Facilitating Muscle-Sparing Thoracotomy

Abstract: The muscle-sparing thoracotomy technique preserves the latissimus dorsi and serratus anterior muscles and provides excellent exposure for most thoracic and mediastinal operations. It also reduces postoperative pain and complications, and preserves pulmonary function. The technique has been developed further to facilitate subcutaneous dissection by insufflation of air from a syringe connected to a large-bore needle via a 3-way tap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…All authors in this group [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] noted occasional need to divide lower attachments of serratus anterior muscle to obtain adequate exposure (broken line on Figure 5). Among these 17 references there are six randomized controlled trials of Type III vs. posterolateral thoracotomy.…”
Section: Disadvantagesmentioning
confidence: 99%
“…All authors in this group [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] noted occasional need to divide lower attachments of serratus anterior muscle to obtain adequate exposure (broken line on Figure 5). Among these 17 references there are six randomized controlled trials of Type III vs. posterolateral thoracotomy.…”
Section: Disadvantagesmentioning
confidence: 99%
“…1,10,13,14,17 Most studies concur that there is no difference in operating time between the 2 techniques; opening time is longer in MST but the closing time is shorter compared with the PLT approach, so the overall operating time is equal with either of the techniques. 1,10,17,18 In an attempt to clarify this controversy, several metaanalyses have been performed. A meta-analysis by Uzzaman et al of 12 different studies comparing MST (n = 571) and PLT (n = 512) revealed better shoulder internal rotation in the muscle-sparing group (although there were no differences in shoulder abduction, flexion, or external rotation), decreased postoperative pain on day 7 (but not on days one or 30), and no difference in lung function at 30 days after operation.…”
Section: Introductionmentioning
confidence: 99%